2005
DOI: 10.1593/neo.04535
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profile of Glioblastoma Multiforme Invasive Phenotype Points to New Therapeutic Targets

Abstract: The invasive phenotype of glioblastoma multiforme (GBM) is a hallmark of malignant process, yet molecular mechanisms that dictate this locally invasive behavior remain poorly understood. Gene expression profiles of human glioma cells were assessed from laser capture-microdissected GBM cells collected from paired patient tumor cores and white matter-invading cell populations. Changes in gene expression in invading GBM cells were validated by quantitative reverse transcription polymerase chain reaction (QRT-PCR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
249
1
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(264 citation statements)
references
References 42 publications
8
249
1
6
Order By: Relevance
“…Several works (Sallinen et al, 2000;Khan et al, 2001;Ramaswamy et al, 2001;Rickman et al, 2001;Agrawal et al, 2002;Kim et al, 2002;Veer et al, 2002;Vijver et al, 2002;Boom et al, 2003;Godard et al, 2003;Hunter et al, 2003;Mischel et al, 2003;Nutt et al, 2003;Shai et al, 2003;Sorlie et al, 2003;Freije et al, 2004;Mischel et al, 2004;Hoelzinger et al, 2005;Liang et al, 2005;Nigro et al, 2005;Rich et al, 2005;Somasundaram et al, 2005;Wong et al, 2005) showed the usefulness of utilizing methods of analysis of multiple forms of data including both clinical and multiple genes, to achieve a more precise discrimination of outcomes for individual patients. The same logical use of multiple forms of data and methods of analysis has been applied in the present study to accurately achieve better classification and prediction of glioma patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several works (Sallinen et al, 2000;Khan et al, 2001;Ramaswamy et al, 2001;Rickman et al, 2001;Agrawal et al, 2002;Kim et al, 2002;Veer et al, 2002;Vijver et al, 2002;Boom et al, 2003;Godard et al, 2003;Hunter et al, 2003;Mischel et al, 2003;Nutt et al, 2003;Shai et al, 2003;Sorlie et al, 2003;Freije et al, 2004;Mischel et al, 2004;Hoelzinger et al, 2005;Liang et al, 2005;Nigro et al, 2005;Rich et al, 2005;Somasundaram et al, 2005;Wong et al, 2005) showed the usefulness of utilizing methods of analysis of multiple forms of data including both clinical and multiple genes, to achieve a more precise discrimination of outcomes for individual patients. The same logical use of multiple forms of data and methods of analysis has been applied in the present study to accurately achieve better classification and prediction of glioma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, developed microarray technology has permitted development of multi-organ cancer classification including gliomas (Ramaswamy et al, 2001;Rickman et al, 2001;Kim et al, 2002;Hunter et al, 2003;Mischel et al, 2004), identification of tumor subclasses (Khan et al, 2001;Mischel et al, 2003;Shai et al, 2003;Sorlie et al, 2003;Liang et al, 2005;Nigro et al, 2005;Wong et al, 2005), discovery of progression markers (Sallinen et al, 2000;Agrawal et al, 2002;van de Boom et al, 2003;Godard et al, 2003;Hoelzinger et al, 2005;Rich et al, 2005;Somasundaram et al, 2005) and prediction of disease outcomes (van't Veer et al, 2002;van de Vijver et al, 2002;Nutt et al, 2003;Freije et al, 2004). Unlike clinicopathological staging, molecular staging can predict long-term outcomes of any individual based on gene expression profile of the tumor at diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Neoplastic cells were identified by their nuclear atypia and heteropycnotic staining. Reactive astrocytes were recognized by dendritic morphology of their abundant eosinophilic cytoplasm and large eccentric nuclei (26). Tumors were classified according to the World Health Organization (WHO) criteria (27).…”
Section: Methodsmentioning
confidence: 99%
“…À l'intérieur même d'une sous-population tumorale, les cellules présentent de façon hétérogène des altérations moléculaires, telles que l'amplification de l'EGFR (points oranges), de la MET (points jaunes), du PDGFR (points verts) ou la méthylation du promoteur de MGMT (points bleus). B. Les différentes sous-populations tumorales expriment des gènes différents en faveur d'un comportement biologique différent [19][20][21][22][23][24][25][26][27][28][29] (voir Glossaire pour définition des abréviations).…”
Section: Hétérogénéité Intratumoraleunclassified
“…GFAP et pERK [20] Nestine et pAKT [20] ASPHD2, NFE2L2, LAMC1, CD133 [24] ET-1, IL-8 [26] CD133 [19] IGFBP2 et vimentine [21] Autotaxine, éphrine B3, Bcl-w, PTK 2 [21] Hif1, IL-8 [25] E-sélectine [27] Nestine [28] Stéphine B [22] Cathepsines S et L [22] Gènes de la voie Notch [29] …”
Section: Cellules Initiatrices De Gliome (I)unclassified